Processo de palatalização no português: Lagoa da Pedra e Canabrava-TO - DIAS, Ana Lourdes Cardoso (2009)
This study presents an analysis of the palatalization process of /t/ and /d/ before vowels as [ã] [a], [e], [o] and [u] in examples such as muitxu ~ muito, prefeitxu ~ prefeito, deitxadu ~ deitado, doidzu ~ doido, founded in the Corpus of Lagoa de Pedra and Canabrava, two rural african descent communities located 40 km from the city of Arraias in the State of Tocantins. The survey participants were aged between 54 to 89 years, non-educated or having little knowledge of letters, and were born and grown in site. The methodology used for data collection was based on the model of the sociolinguistic interview, focused on the narratives of personal experience and in the history of the place. The theoretical background discusses the formation of the Portuguese language returning to its roots in Latin, as well as the formation of the Brazilian Portuguese language with focus on linguistics and socio-historical aspects that marked the early years of Portuguese colonization in Brazil, as the contact with indigenous languages and African ones. It also discusses the theories of syllable structure of the Portuguese language in the phonology, according to the linear and nonlinear standards, based on ideas from Camara Jr. (1969, 1977), Dubois (2004) and Selkirk (1982), similarly, the consonant and vowel system and the process of palatalization from Latin to Portuguese and the description of this process in the current Portuguese based on structuralist, generative and autossegmental models. To data description it was taken into account internal factors to the language that could possible foment, or discourage, the palatalization process of /t/ e /d/ such as: the following phonological context; the preceding phonological context; syllable position in the word and tone. The data analysis was divided into two parts, in which the first part is the phonological analysis of the process of palatalization on the model proposed by the geometry of phonological features theory, according to Bisol and Hora (1993), Hora (1993), based on Clements's proposal (1985). The second, based on claims of historical linguistics, with respect to variation, preservation and linguistic change, analyzes the process in a historical-evolutionary scale. In this perspective, the historical phonetics is of utmost importance for the discussions, (COUTINHO, 1976; ELIA, 1979; BUENO, 1958)